The lion, the witch, and the wardrobe - Lewis, C. S. (Clive Staples) 1898-1963 (Lewis, C. S. (Clive Staples) 1898-1963. Chronicles of Narnia (HarperCollins (Firm)), 1994)
Four English schoolchildren find their way through the back of a wardrobe into the magic land of Narnia and assist Aslan, the golden lion, to triumph over the White Witch, who has cursed the land with eternal winter.